Nest excavators’ learning walks in the Australian desert ant Melophorus bagoti - Sudhakar Deeti; Donald James McLean; Ken Cheng (Animal Cognition)
Abstract The Australian red honey ant, Melophorus bagoti, stands out as the most thermophilic ant in Australia, engaging in all outdoor activities during the hottest periods of the day during summer months. This species of desert ants often navigates by means of path integration and learning landmark cues around the nest. In our study, we observed the outdoor activities of M. bagoti workers engaged in nest excavation, the maintenance of the nest structure, primarily by taking excess sand out of the nest. Before undertaking nest excavation, the ants conducted a single exploratory walk. Following their initial learning expedition, these ants then engaged in nest excavation activities. Consistent with previous findings on pre-foraging learning walks, after just one learning walk, the desert ants in our study demonstrated the ability to return home from locations 2 m away from the nest, although not from locations 4 m away. These findings indicate that even for activities like dumping excavated sand within a range of 5–10 cm outside the nest, these ants learn and utilize the visual landmark panorama around the nest.